Electrochemical Deposition of ZnO Thin Films on to Tin(IV) oxide:Fluorine - Yilmaz, M.; Turgut, G.; Aydin, S.; Ertugrul, M. (Asian Journal of Chemistry, 2012)
In this study firstly, fluorine doped tin(IV) oxide thin film was formed on glass substrate by spray pyrolysis method. Then ZnO film was growth by electrochemical deposition onto conductive fluorine doped tin(IV) oxide film sprayed and ZnO thin films were annealed in air at 450 ºC. The crystal structures of fluorine doped tin(IV) oxide and ZnO thin films was characterized with XRD. It was identified that fluorine doped tin(IV) oxide and ZnO films had cassiterite and hexagonal wurtzite structure, respectively. Surface morphology of annealed and unannealed ZnO was characterized by SEM. According to SEM analysis, annealed ZnO thin film compared to the unannealed film has a homogeneous surface morphology and small grains. Also, electrical measurement of the obtained FTO/ZnO/Au structure investigated by I-V measurements. Series resistance, barrier height and ideality factor values of obtained structure were calculated and discussed from I-V measurements.